Genetic and environmental contributions to the association between mood disorder and periodontal disease: A cross‐sectional study among female twins in the UK. (20th January 2019) - Kurushima, Yuko; Bowyer, Ruth; Ide, Mark; Hughes, Francis J.; Steves, Claire J.
Abstract: Aim: This study aimed to investigate the factors associated with periodontal traits considering genetic and environmental background in predominantly older female twins. Methods: This was a cross‐sectional study using self‐reported questionnaires for periodontal traits in TwinsUK. Age‐adjusted and age‐stratified multivariate analyses were conducted for all twins. Subsequently, co‐twin control analysis within genetically identical twins who were discordant for periodontal traits was performed by controlling for genetic confounders. Results: Data of twins aged 20–91 were available in 4, 143 individuals for self‐reported periodontitis and 4, 244 for gum bleeding. Age‐adjusted model showed increasing risk in the following: smoking, anxiety/stress and depression for both periodontal traits. Within discordant monozygotic (MZ) twins (514 individuals for periodontitis and 754 for gum bleeding), the association of anxiety/stress remained significant for both periodontitis (OR 1.60, CI: 1.02–2.52) and gum bleeding (OR 1.60, CI: 1.06–2.40). A significant relationship for depression remained for periodontitis (OR 1.68, CI: 1.04–2.70), but it was no longer significant for gum bleeding. Age stratification showed that the association of mood disorders with periodontal traits was generally stronger in older group. Conclusions: Multivariate analysis among discordant MZ female twins found mood disorders were independently associated with periodontal traits, suggesting that genetic/early‐life environmental factors may not explain this association.